The Prevalence and Use of Walking Loops in Neighborhood Parks: A National Study - Cohen, Deborah A.; Han, Bing; Evenson, Kelly R.; Nagel, Catherine; McKenzie, Thomas L.; Marsh, Terry; Williamson, Stephanie; Harnik, Peter (Environmental health perspectives, 2017)
Previous studies indicate that the design of streets and sidewalks can influence physical activity among residents. Park features also influence park use and park-based physical activity. Although individuals can walk on streets and sidewalks, walking loops in parks offer a setting to walk in nature and to avoid interruptions from traffic. Here we describe the use of walking loops in parks and compare the number of park users and their physical activity in urban neighborhood parks with and without walking loops. We analyzed data from the National Study of Neighborhood Parks in which a representative sample of neighborhood parks (n = 174) from 25 U.S. cities with > 100,000 population were observed systematically to document facilities and park users by age group and sex. We compared the number of people and their physical activity in parks with and without walking loops, controlling for multiple factors, including park size, facilities, and population density. Overall, compared with parks without walking loops, on average during an hourly observation, parks with walking loops had 80% more users (95% CI: 42, 139%), and levels of moderate-to-vigorous physical activity were 90% higher (95% CI: 49, 145%). The additional park use and park-based physical activity occurred not only on the walking loops but throughout the park. Walking loops may be a promising means of increasing population level physical activity. Further studies are needed to confirm a causal relationship. Citation: Cohen DA, Han B, Evenson KR, Nagel C, McKenzie TL, Marsh T, Williamson S, Harnik P. 2017. The prevalence and use of walking loops in neighborhood parks: a national study. Environ Health Perspect 125:170-174; http://dx.doi.org/10.1289/EHP293.